2011
DOI: 10.1186/1746-4358-6-9
|View full text |Cite
|
Sign up to set email alerts
|

An observational study of associations among maternal fluids during parturition, neonatal output, and breastfed newborn weight loss

Abstract: BackgroundNewborn weight measurements are used as a key indicator of breastfeeding adequacy. The purpose of this study was to explore non-feeding factors that might be related to newborn weight loss. The relationship between the intravenous fluids women receive during parturition (the act of giving birth, including time in labour or prior to a caesarean section) and their newborn's weight loss during the first 72 hours postpartum was the primary interest.MethodsIn this observational cohort study, we collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 29 publications
1
48
0
1
Order By: Relevance
“…, 27 The infusion of 1.200mL to more than 2.500mL of fluids to the mother, at a cesarean section or vaginal delivery with analgesia,19 determines hypervolemia in newborns and increases diuresis on the first day of life 227 Much of the weight loss of these newborns is observed on the first day 2…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, 27 The infusion of 1.200mL to more than 2.500mL of fluids to the mother, at a cesarean section or vaginal delivery with analgesia,19 determines hypervolemia in newborns and increases diuresis on the first day of life 227 Much of the weight loss of these newborns is observed on the first day 2…”
Section: Discussionmentioning
confidence: 99%
“…, 27 The infusion of 1.200mL to more than 2.500mL of fluids to the mother, at a cesarean section or vaginal delivery with analgesia,19 determines hypervolemia in newborns and increases diuresis on the first day of life 227 Much of the weight loss of these newborns is observed on the first day 219 In a review of the subject19 evidence was found in eight studies that associated weight loss with excess fluids offered to the mother in exclusively breastfed newborns.…”
Section: Discussionmentioning
confidence: 99%
“…Noel-Weiss et al were aware of the controversy around routine newborn weight measurements [12]. The researchers were prepared to stop the study if the participants were distressed or showing signs that frequent weight measurements were influencing how they were managing breastfeeding (e.g., use of formula supplementation).…”
Section: Methodsmentioning
confidence: 99%
“…In a recent study about newborn weight loss [12], participants weighed their infants for 14 days as part of the data collection. Participants in the original study received a portable electronic baby scale, provided by the researcher, after the birth of their babies.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation